Transformer Parameters Monitoring System using MATLAB Simulink - Ashish C. Jangam; Prof. D.G. Chougule; Prof. A.S. Mali (International Journal of Engineering and Management Research, 2018)
Transformer is an important component of an electrical distribution system. Hence it is important to monitor transformers for problems before faults occur. This system is about design and implementation of embedded system to monitor and record key parameters of a distribution transformer like load currents,voltage and temperature. It is installed at the distribution transformer site and the above parameters are recorded using the analog to digital converter (ADC) of the embedded system. The obtained parameters are processed and recorded in the system memory. If any abnormality or an emergency situation occurs the system takes immediate action to avoid it. This system will help the transformers to operate smoothly and identify problems before any failure. proposed system is low cost, easy to use capable of monitoring and displaying data using matlab[1,6].